2016
DOI: 10.1080/03081087.2016.1201040
|View full text |Cite
|
Sign up to set email alerts
|

Sub-defect of product of doubly substochastic matrices

Abstract: The sub-defect of an n × n doubly substochastic matrix S, denoted by sd(S), is defined to be the smallest integer k such that there exists an (n + k) × (n + k) doubly stochastic matrix containing S as a submatrix. Let A and B be arbitrary doubly substochastic matrices. We show that AB is also a doubly substochastic matrix and max{sd(A), sd(B)} ≤ sd(AB) ≤ min{n, sd(A) + sd(B)}. ARTICLE HISTORY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The first way to partition ω n is induced by a characteristic of doubly substochastic matrices called sub-defect [7,6,5]. Definition 2.1.…”
Section: Three Different Partitions Of ω Nmentioning
confidence: 99%
“…The first way to partition ω n is induced by a characteristic of doubly substochastic matrices called sub-defect [7,6,5]. Definition 2.1.…”
Section: Three Different Partitions Of ω Nmentioning
confidence: 99%
“…It is the smallest integer k such that there exists an (n + k) × (n + k) doubly stochastic matrix containing B as a submatrix. It has been shown that the sub-defect can be calculated easily by taking the ceiling of the difference of the size of the matrix and the sum of all entries (see [4], [5] and [6]). Diagonal Sums of Doubly Substochastic Matrices Theorem 1.1.…”
mentioning
confidence: 99%
“…Actually, if A, B ∈ ω n , then AB ∈ ω n (Proposition 2.4 in [5]). We can evaluate the extreme values of h(AB) and l(AB).…”
mentioning
confidence: 99%